2004
DOI: 10.1074/jbc.m404849200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage to Specific Proteins in Replicative and Chronological-aged Saccharomyces cerevisiae

Abstract: Oxidative modifications of cellular components have been described as one of the main contributions to aged phenotype. In Saccharomyces cerevisiae, two distinct life spans can be considered, replicative and chronological. The relationship between both aging models is still not clear despite suggestions that these phenomena may be related. In this work, we show that replicative and chronological-aged yeast cells are affected by an oxidative stress situation demonstrated by increased protein carbonylation when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
168
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(184 citation statements)
references
References 53 publications
16
168
0
Order By: Relevance
“…Other carbonylated proteins, including Tsa1p, Ahp1p, Hsp26p, Adh3p, and Mcr1p, were uniquely identified in the Δidp2Δzwf1 mutant. Interestingly, several of the proteins (including Eno1p, Eno2p, Fbpa1p, Adh1p, Tdh, and other heat shock proteins) identified in this and related studies were also found to be carbonylated in response to replicative and/or chronological aging [26]. Because of these similarities in patterns of carbonylation, examination of the state of cysteine side-chain oxidation and of levels of NADP (H) as a function of yeast cellular aging would clearly be of interest for future studies.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Other carbonylated proteins, including Tsa1p, Ahp1p, Hsp26p, Adh3p, and Mcr1p, were uniquely identified in the Δidp2Δzwf1 mutant. Interestingly, several of the proteins (including Eno1p, Eno2p, Fbpa1p, Adh1p, Tdh, and other heat shock proteins) identified in this and related studies were also found to be carbonylated in response to replicative and/or chronological aging [26]. Because of these similarities in patterns of carbonylation, examination of the state of cysteine side-chain oxidation and of levels of NADP (H) as a function of yeast cellular aging would clearly be of interest for future studies.…”
Section: Discussionmentioning
confidence: 51%
“…(b) Many of these fluorescein-labeled proteins exhibit multiple isoforms (labeled with letters) with slight differences in apparent molecular weights and isoelectric points. Multiple isoforms are common in two-dimensional analyses of yeast cellular proteins [24][25][26][27][28]. (c) Many of the same proteins were found to contain disulfide bonds in oleate-shifted cells (gels not shown).…”
Section: Assays For Disulfide Bondsmentioning
confidence: 99%
“…Pgk1p was abundantly expressed in cells grown in glucose, and transcription was increased by heat shock (Piper et al, 1986) and regulated by the transcription factors Rab1p, Abf1p, and Reb1p (Packham et al, 1996). In particular, enolase and Ssb protein are major targets of protein damage in WT yeast cells exposed to oxidative stress (Cabiscol et al, 2000;Reverter-Branchat et al, 2004). Downregulation of glycolytic enzymes by irreversible protein oxidation impairs glucose utilization and this effect is correlated with enhanced gluconeogenic and energy storage pathways, and causes an imbalance in proteostasis, which plays a role in protein translocation, folding, and assembly (Reverter-Branchat et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, enolase and Ssb protein are major targets of protein damage in WT yeast cells exposed to oxidative stress (Cabiscol et al, 2000;Reverter-Branchat et al, 2004). Downregulation of glycolytic enzymes by irreversible protein oxidation impairs glucose utilization and this effect is correlated with enhanced gluconeogenic and energy storage pathways, and causes an imbalance in proteostasis, which plays a role in protein translocation, folding, and assembly (Reverter-Branchat et al, 2004). Therefore, a high accumulation of metabolic enzymes in the TF yeast cells is important for the production of ATP and NADPH because NADPH serves as a reducing agent in thioredoxin systems containing Ahp1p, whereas ATP is used as a substrate of molecular chaperones such as Ssb2 protein to prevent protein aggregation or refolding of damaged proteins during H 2 O 2 stress.…”
Section: Discussionmentioning
confidence: 99%
“…A great number of recent reports confirm the Harman "free radical theory of ageing" proposed some fifty years ago although many unknown details still remain. For example, although many proteins are found in an oxidized state during cell senescence [1,2,3,4,5], the identity of the more relevant targets of oxidation and how their modification can affect cell lifespan remains unknown [6]. In the budding yeast S. cerevisiae two types of lifespan can be measured: replicative and chronological.…”
Section: Introductionmentioning
confidence: 99%